2017
DOI: 10.18632/oncotarget.23258
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine, a broad-spectrum antiviral drug, suppresses enterovirus infections through innate immunity induced by the inhibition of pyrimidine biosynthesis and nucleotide depletion

Abstract: Gemcitabine, an anti-cancer chemotherapy drug, has additionally shown the antiviral activity against a broad range of viruses and we also have previously reported its synergistic antiviral activity with ribavirin against enteroviruses. As a cytidine analog, gemcitabine has been reported to have an inhibitory activity on the pyrimidine biosynthesis. In addition, a few inhibitors of the pyrimidine biosynthesis have shown to induce the innate immunity in a yet-to-be-determined manner and inhibit the virus infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 43 publications
5
29
0
1
Order By: Relevance
“…We also confirmed previously reported activities of chloroquine against CHIKV and ZIKV, mycophenolic acid against CHIKV and RRV, fluoxetine, pirlindole and dibucaine against EV1, BCX4430, lopinavir and hydroxichloroquine against ZIKV, as well as gemcitabine against EV1, FLUAV, ZIKV and HSV-1 (Cao et al, 2017;Delogu and de Lamballerie, 2011;Delvecchio et al, 2016;Denisova et al, 2012;Julander et al, 2017;Kang et al, 2015;Khan et al, 2011;Kuivanen et al, 2017;Lee et al, 2017;Soderholm et al, 2016;Ulferts et al, 2016;Yuan et al, 2017) (Fig. 4).…”
Section: Discussionsupporting
confidence: 91%
“…We also confirmed previously reported activities of chloroquine against CHIKV and ZIKV, mycophenolic acid against CHIKV and RRV, fluoxetine, pirlindole and dibucaine against EV1, BCX4430, lopinavir and hydroxichloroquine against ZIKV, as well as gemcitabine against EV1, FLUAV, ZIKV and HSV-1 (Cao et al, 2017;Delogu and de Lamballerie, 2011;Delvecchio et al, 2016;Denisova et al, 2012;Julander et al, 2017;Kang et al, 2015;Khan et al, 2011;Kuivanen et al, 2017;Lee et al, 2017;Soderholm et al, 2016;Ulferts et al, 2016;Yuan et al, 2017) (Fig. 4).…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, the activation of ISGs was well-correlated with the inhibition of pyrimidine biosynthesis, suggesting a link between pyrimidine biosynthesis and innate immunity. Similar phenomena in terms of ISG activation have been previously reported with a few compounds out of several purine or pyrimidine biosynthesis inhibitors that had antiviral activity, as summarized in Table 2 [ 6 , 10 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Innate Immune Activation By Purine and Pyrimidine Biosyntsupporting
confidence: 82%
“…Most studies regarding the antiviral activity of gemcitabine lack experimental evidence of the mode of action. However, our group has recently reported that gemcitabine had an anti-EV effect by targeting the salvage pathway of pyrimidine biosynthesis [ 23 ]. Moreover, gemcitabine strongly induced the expression of several ISGs including CXCL10, IRF7, IRF9, IFIT1, and DDX58, which were the major effectors in the innate immunity that defended the host against the virus infection.…”
Section: Innate Immune Activation By Purine and Pyrimidine Biosyntmentioning
confidence: 99%
“…Gemcitabine was primarily manufactured in 1980 by Larry Hertel's group at Eli Lilly and Company to be used as an anti-viral drug against enteroviruses [Coxsackievirus B3 (CVB3)]. The drug was also used against CVB3, EV71, human rhinoviruses (HRVs), human immunodeficiency virus (HIV), hepatitis C virus (HCV), poliovirus, influenza virus, ZIKV and MERS-CoV [104,105]. It was then pre-clinically tested for its anti-tumour attribute.…”
Section: Antimetabolitesmentioning
confidence: 99%